IMPLEMENTASI PRINSIP GOOD GOVERNANCE TERHADAP PELAYANAN PUBLIK PADA MASA COVID-19 DI KANTOR DESA - Zulaykhah, Alqori (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study is to analyze whether accountability, transparency and participation in public services partially or simultaneously have an influence on public services in village offices throughout Bagor District, Nganjuk Regency. This study uses,,quantitative methods. The sampling technique in this study used purposive sampling taken with certain criteria amounting to 90 people. Data collection techniques using a questionnaire. The analysis technique used in this research is multiple linear regression technique. The kresults of this research show that 1) partial kaccountability has no effect on public services. 2) transparency partially affects public services. 3) participation partially affects public services. 4) accountability, transparency, and participation simultaneously affect public services. It is hoped that the village office staff in the Bagor sub-district kwill carry out the principles of Good Governance well.